Demons - Nadim, Nesar (Dhaka : Daily Star Books, 2015)
Novel.

"Bangladeshi-American Saad Haque, his wife, and their young son live in Uxbridge, a remote Texas town. Stress has made Saad lash out at his family in the past. When he remembers what he did - what he almost did - it turns his blood to ice. One day, a strange storm strikes, cutting off the town from the outside world. Dozens of people transform into nightmarish creatures with razor-sharp jaws and claws. In fifteen minutes, the population of Uxbridge is reduced from about twelve hundred to a hundred. Blood flows down the gutters. Corpses and body parts litter the streets. Saad, his family, and a group of survivors fight to stay alive. However, there is something much worse than the creatures lurking in the dark. To face it, Saad must face his own nightmares, his own... demons."--Back cover.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School, BRAC University
Keywords: Bangladeshi fiction (English).; Bangladeshi literature (English).; Horror fiction